Levamisole and surgery in bronchial carcinoma patients: increase in deaths from cardiorespiratory failure. Issue 1 (February 1979) - Anthony, H M; Mearns, A J; Mason, M K; Scott, D G; Moghissi, K; Deverall, P B; Rozycki, Z J; Watson, D A
Abstract : Life table analysis of early entry to this randomised blind trial of 318 patients has shown a significantly poorer survival for resected lung cancer patients treated with levamisole for three days before operation and three days a fortnight thereafter than for placebo-treated controls. This excess was largely due to deaths that had been attributed to operation or other causes (non-cancer deaths), most occurring in the six weeks after operation. In the 99 resected patients treated with levamisole there was a 15% excess of deaths in this category, compared with the placebo-treated controls. Extensive analysis excluded maldistribution of patients between the groups as a cause of this difference. Many more died in respiratory distress, mostly without clear cause, in the levamisole group. Antibody (lgG) reacting with myocardial sarcolemma or sarcoplasm was found in the only serum samples available for testing which were drawn from patients during the syndrome. The findings are in keeping with a primary effect on the heart, possibly involving an autoimmune mechanism. The effect has not been noted in other trials.